On the Generalized Cauchy Problem for the Evolutionary Equation with Operator of Fractional Differentiation - Horodets’kyi, V.V.; Martynyuk, O.V.; Petryshyn, R.I (Journal of Mathematical Sciences, 2022)
We prove the well-posed solvability of the nonlocal problem multipoint in time for the evolutionary equation with operator of fractional differentiation and initial function, which is an element of the space of generalized distribution-type functions.